2011 3rd IEEE International Memory Workshop (IMW) 2011
DOI: 10.1109/imw.2011.5873223
|View full text |Cite
|
Sign up to set email alerts
|

Switching by Ni Filaments in a HfO2 Matrix: A New Pathway to Improved Unipolar Switching RRAM

Abstract: HfO 2 -based resistive RAM (RRAM) devices have received intensive research attention in the recent years. Most of the HfO 2 -based RRAM system demonstrates promising performance in bipolar mode. However, HfO 2 -based RRAM devices in unipolar mode so far, still suffers from low endurance (<500 cycles), and non-integratable electrode materials such as Pt or Au. In this work, CMOS-compatible Ni-containing electrodes / HfO 2 / TiN stacks were demonstrated switching in unipolar mode, with promising endurance >10 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…However, for the bipolar case, the HRS drain current registered is larger than the fresh case (increment of ~75% in this measure). Then, for unipolar and bipolar switching in pMOSFET transistors and bipolar in nMOSFETs a positive charge trapping in the bulk dielectric at the HRS is observed, in agreement with [11,16]. This positive charge trapping produces a positive drain current shift respect the fresh one in these cases, in accordance with the negative threshold voltage shifts observed in fig.…”
Section: Impact On the Transistor Characteristicssupporting
confidence: 83%
See 1 more Smart Citation
“…However, for the bipolar case, the HRS drain current registered is larger than the fresh case (increment of ~75% in this measure). Then, for unipolar and bipolar switching in pMOSFET transistors and bipolar in nMOSFETs a positive charge trapping in the bulk dielectric at the HRS is observed, in agreement with [11,16]. This positive charge trapping produces a positive drain current shift respect the fresh one in these cases, in accordance with the negative threshold voltage shifts observed in fig.…”
Section: Impact On the Transistor Characteristicssupporting
confidence: 83%
“…The cases in which the RS phenomenon was successfully achieved are repetitive for at least 10 cycles. Some studies have reported that while the unipolar switching is related to the Ni diffusion from the gate electrode, the bipolar switching is mainly dominated by diffusion of oxygen vacancies in the conductive filament [11,12]. However, recent works have shown that when RS is studied in transistors, the diffusion of Ni atoms into the dielectric can occur from the gate electrode or from the NiSi electrodes of drain and source (Figure 4) leading to the observation of unipolar and bipolar switching [13].…”
Section: Polarity Dependence Of the Rs Phenomenonmentioning
confidence: 99%
“…This clearly suggests the importance of Ni in the switching, especially the variation between S01 and S02 caused by 1-nm Ni. Moreover, there is no clear indication of Ni diffusion through the~10-nm HfO X layer from the EDX analyses, consistent with TOF-SIMS results from similar stacks [10]. Therefore, we believe NiO X and Ni involvement at the interface, rather than Ni filaments through the switching layer [10], [12], would play the key role for the unipolar switching shown here.…”
Section: B Electrical/switching Propertiessupporting
confidence: 81%
“…In addition, both unipolar and bipolar switching modes have been observed from the Ni silicide samples, similarly as reported in [10]. To make a direct comparison with S02, the unipolar switching with positive bias on top of Ni-containing electrodes will be focused on in this letter, and more detailed analyses of different switching can be found elsewhere [11].…”
Section: B Electrical/switching Propertiesmentioning
confidence: 59%
“…The unipolar switching phenomenon in Ni/HfO 2 /Si devices [3] has been recently analyzed by real time TEM micrographs [4]. The SET process has been attributed to the formation of Ni-based conductive filaments (CFs), owing to oxygen ion drift and subsequent Ni diffusion/migration from the top metal electrode into the dielectric [4][5][6]. In the RESET process, a partial dissolution of the CFs takes place due to thermally enhanced diffusion of Ni atoms induced by joule heating [7,8].…”
Section: Methodsmentioning
confidence: 99%